A floristic survey of Fair Isle. (2nd September 2017) - Quinteros Peñafiel, C. V.; Riddiford, N. J.; Twyford, A. D.
Abstract : Fair Isle is a small isolated island located off the northern tip of Great Britain. Recognised internationally for rare migratory birds and important seabird colonies, the flora of Fair Isle has received far less attention. To rectify this, we present the first comprehensive floristic study of the island. A botanical survey was performed for each monad, and habitat information was collated following the NCC Phase 1 habitat survey method. These data were compiled to give a comprehensive checklist of 318 species, classified into 31 orders, 68 families and 191 genera according to APG IV. Of the total number of species, 255 are native to Great Britain and the remaining 63 are aliens. The list includes 10 species under threat, seven nationally scarce and one nationally rare species. Our results reveal that even though Fair Isle is about 200 times smaller than the full archipelago of Shetland, it holds over one-third the number of species. The island is also notable for its complex mosaic of habitats, which include a range of communities that are rare or under threat elsewhere in the British Isles. We provide a detailed commentary of island diversity, and recommendations for future monitoring to record changes in land-use and the effects of climate change.